The Relationship Between Home Environment and the Incidence of Ari Disease in Coastal Communities on Maitara Island, Tidore Islands - Hakim, Abdul (Journal of Midwifery and Nursing, 2024)
Clean and healthy living behavior population is one effort Prevent the occurrence of ARI by pay attention to the house and healthy environment. This research was a quantitative study with cross sectional design. Sample was the a coastal community on Maitara Island North Tidore District. The total sample was 30 people, It was determined using purposive sampling method. Data was collected by interview and direct observation. Questioned was used as the instrument. Data analyzed using univariate and chi square analysis. Data analysis had been done using SPSS software. The results of bivariate analysis using the chisquare test, obtaining a p value of 0.000 (p<0.05), illustrates that home environmental factors have a significant relationship with a history of ARI. The home cleanliness is a crucial aspect of reducing the incidence of acute respiratory Infection.